PENGUATAN KELEMBAGAAN SENTRA INDUSTRI KECIL MENENGAH PADA PERKUMPULAN JAJAN KHAS SOLO 19, KADIPIRO SURAKARTA - Sutiyo Sutiyo; Dora Kusumastuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The JKS 18 Association is one of the food-producing centers in Surakarta. This association needs to get institutional and product strengthening to increase competitiveness in the global era. The methods used are lectures and mentoring. Hasil Mitra has a registered legal entity at the Ministry of Public Affairs and Human Rights and has the legality of being a PIRT. Keywords: Perkumpulan IKM, JKS 18, Sentra Surakarta